ChemInform Abstract: Applying Quantitative Microstructure Control in Advanced Functional Composites. Issue 30 (29th July 2014) - Heinz, Nicholas A.; Ikeda, Teruyuki; Pei, Yanzhong; Snyder, G. Jeffrey
Abstract Review: 118 refs.